Using Artificial Neural Network Models For Forecasting & Comparison - ناظم ايفان علاء (Journal of Economics and Administrative Sciences, 2009)
The Artificial Neural Network methodology is a very important & new subjects that build’s the models for Analyzing, Data Evaluation, Forecasting & Controlling without depending on an old model or classic statistic method that describe the behavior of statistic phenomenon, the methodology works by simulating the data to reach a robust optimum model that represent the statistic phenomenon & we can use the model in any time & states, we used the Box-Jenkins (ARMAX) approach for comparing, in this paper depends on the received power to build a robust model for forecasting, analyzing & controlling in the sod power, the received power come from the generation state company & to be considered as Exogenous variables to two methodologies, the sales activity in the General Company of Baghdad Electricity Distribution divides it’s work to three stages: • Account the Sold Power. • Account the Value of the Sold Power. • Account the Cash Received.